2013
DOI: 10.1016/j.ahj.2012.11.013
|View full text |Cite
|
Sign up to set email alerts
|

The association of fetal cerebrovascular resistance with early neurodevelopment in single ventricle congenital heart disease

Abstract: Background Children with congenital heart disease are at risk for impaired neurodevelopment (ND). We investigated the association of fetal cerebrovascular resistance with ND in patients with single ventricle lesions. Methods In the Single Ventricle Reconstruction (SVR) and Infant Single Ventricle trials, 14-month ND was assessed using the Bayley Scales of Infant Development II. We investigated associations between ND scores and fetal middle cerebral artery pulsatility index (MCA-PI) z-scores, a Doppler-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 19 publications
1
72
0
1
Order By: Relevance
“…No other subtypes were associated with disproportionately smaller head circumference, as previously suggested in other studies of TOF, HLHS, or aortic arch hypoplasia. 13,15,20,[41][42][43] We found disproportionately larger head circumferences relative to birth weight in major VSDs and other less severe subtypes of CHD. No previous studies have reported such associations.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…No other subtypes were associated with disproportionately smaller head circumference, as previously suggested in other studies of TOF, HLHS, or aortic arch hypoplasia. 13,15,20,[41][42][43] We found disproportionately larger head circumferences relative to birth weight in major VSDs and other less severe subtypes of CHD. No previous studies have reported such associations.…”
Section: Discussionmentioning
confidence: 81%
“…Ultrasound studies have demonstrated brain sparing in fetuses with CHD, 13,16,17,19,42,43 and MRI studies have demonstrated decreased fetal cerebral volume before birth. 7,14 Recently, measures of fetal cerebral oxygenation were directly linked to prenatal brain volume.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that CHD, resulting in abnormal cerebral blood flow and oxygen saturation, is frequently associated with impaired development of the fetal brain [2,3,16,17]. Postnatally abnormal cerebral perfusion and oxygen saturation persist in the preoperative and in the perioperative period and are linked to cerebral white matter injury [2,16,17,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Congenital heart disease (CHD) is associated with an increased risk of neurodevelopmental deficits [1]. Already in fetal life altered haemodynamics and reduced cerebral oxygenation due to the congenital heart defect may result in impaired brain growth and altered structural and cellular maturation particularly of the white matter [1][2][3]. Altered brain development increases cerebral vulnerability in the perioperative period [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo, Williams et al (2012a) defienden que los niños con CC tienen un alto riesgo de padecer problemas neurocognitivos, incluyendo dificultades de aprendizaje, problemas en la conducta y lentitud mental.…”
Section: Introductionunclassified